2017
DOI: 10.1186/s12862-017-1084-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple markers, niche modelling, and bioregions analyses to evaluate the genetic diversity of a plant species complex

Abstract: BackgroundThe classification of closely related plants is not straightforward. These morphologically similar taxa frequently maintain their inter-hybridization potential and share ancestral polymorphisms as a consequence of their recent divergence. Under the biological species concept, they may thus not be considered separate species. The Petunia integrifolia complex is especially interesting because, in addition to the features mentioned above, its taxa share a pollinator, and their geographical ranges show m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 90 publications
3
20
0
Order By: Relevance
“…The most suitable areas during the LGM occurred in the south and southeast of Brazil, mainly from 23°S to 27°S from the Santa Catarina to São Paulo states (Fig. D), making evident that the appropriate ranges for V. incurvata occupation in the continental shelf during the LGM are now submersed, as similarly observed in other studies (Pinheiro et al., ; Thode et al., ; Leite et al., ; Segatto et al., ). Our V. incurvata results for MH showed that the suitable areas are very similar to those observed in the present (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most suitable areas during the LGM occurred in the south and southeast of Brazil, mainly from 23°S to 27°S from the Santa Catarina to São Paulo states (Fig. D), making evident that the appropriate ranges for V. incurvata occupation in the continental shelf during the LGM are now submersed, as similarly observed in other studies (Pinheiro et al., ; Thode et al., ; Leite et al., ; Segatto et al., ). Our V. incurvata results for MH showed that the suitable areas are very similar to those observed in the present (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Pearson's correlation between the variables was calculated using the RASTER package. We selected bioclimatic variables with low correlation ( R ≤ 0.75) and that presented a high percentage of importance to the model in a preliminary run (Nakazato et al., ; Segatto et al., ). We used cross‐validation to evaluate the species’ distribution model, using 10 replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, our observations are tentative in character and need to be tested on a large-scale study, possibly involving auxiliary molecular evidence (e.g., sequencing of chosen informative or ''barcoding'' loci; CBOL Plant Working Group, 2009), as well as descriptive taxonomy using the geographical and ecological methods (Duminil and Di Michele, 2009;Reed and Frankham, 2001). Several reports successfully used the Amplified Fragment Length Polymorphism as molecular markers neutral in character and of nuclear origin, for plant species delimitation (Chen et al, 2013;Meudt et al, 2009;Segatto et al, 2017) or SSR alike (Chen et al, 2013;Dupuis et al, 2012;Meudt et al, 2009). In particular, the eSSR markers may be of interest due to their conservation and informativeness among the closely related species (Ellis and Burke, 2007).…”
Section: Resultsmentioning
confidence: 89%
“…In particular, the eSSR markers may be of interest due to their conservation and informativeness among the closely related species (Ellis and Burke, 2007). SSRs also help increase the power of low taxonomic level distinction in agreement with the ''one marker is not enough'' approach (Dupuis et al, 2012;Segatto et al, 2017). The tentative assignment of the commercial cultivar Pierre to the large cluster with samples of vars.…”
Section: Resultsmentioning
confidence: 99%
“…It has been argued that hybrid populations are not worth conserving because hybridization events may be due to anthropogenic influences such as the introduction of plants and animals, habitat fragmentation and habitat modification (Allendorf et al 2001). The use of molecular methods can help to clarify the taxonomic status of populations of closely related rare plant species (Turchetto et al 2015;Segatto et al 2017).…”
Section: Introductionmentioning
confidence: 99%